Correlation of Oxygen Saturation on Pulse Oximeter With Chest CT Severity Score in Young Adult Covid-19 Patients - Khalid, Bassam; Saleem, Taimoor; Naseer, Umer; Hashmat, Asif; Uttra, Khurshid Muhammad; Khan, Najib Ullah (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the association between Computerized Tomography severity score and oxygen saturation by pulse oximeter in patients of COVID-19. Study Design: Cross sectional study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Apr 2021. Methodology: CT severity score was calculated for all patients who had undergone Chest CT scan. The oxygen saturation by pulse oximeter was noted at admission. Spearman rank correlation was calculated between the CT severity score and oxygen saturation on pulse oximeter. Results: There were 203 patients in this study. Among them, 124(61.1%) were male and 74(38.9%) females. The greater proportion of the patients, 138(68%) were between 36-55 years old, and 65(32%) were between 18-35 years old. There were 130(64%) patients who had low CT severity score, 73(36%) had high CT severity score. Among 73 patients who had high CT severity score, 67(91.7%) had shortness of breath (p-value<0.001), 48(66%) had fever (p-value=0.021), and 53(72.6%) belonged to the older age group of patients (p-value=0.0294). Statistically significant negative correlation between Computerized Tomography severity score and oxygen saturation was noted (r rho=−0.264, p= 0.01). Conclusions: Our study provided evidence that there is a negative correlation between the Computerized Tomography severity score and oxygen saturation by pulse oximeter.